Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1051/0004-6361/201526081
|View full text |Cite
|
Sign up to set email alerts
|

Making the observational parsimonious richness a working mass proxy

Abstract: Richness, i.e., the number of bright cluster galaxies, is known to correlate with the cluster mass, however, to exploit it as mass proxy we need a way to estimate the aperture in which galaxies should be counted that minimizes the scatter between mass and richness. In this work, using a sample of 39 clusters with accurate caustic masses at 0.1 < z < 0.22, we first show that the scatter between mass and richness derived from survey data is negligibly small, as small as best mass proxies. The scatter turns out t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
40
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 25 publications
(49 citation statements)
references
References 48 publications
(75 reference statements)
8
40
0
1
Order By: Relevance
“…This 0.02 dex intrinsic scatter in mass is comparable to or better than the values derived for other proxies, such as the integrated pressure Y SZ or pseudo pressure Y X , X-ray luminosity L X , gas mass M gas , and stellar mass (Andreon 2015 (Andreon 2015), and L X (Andreon & Hurn 2010). We note that Eq.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…This 0.02 dex intrinsic scatter in mass is comparable to or better than the values derived for other proxies, such as the integrated pressure Y SZ or pseudo pressure Y X , X-ray luminosity L X , gas mass M gas , and stellar mass (Andreon 2015 (Andreon 2015), and L X (Andreon & Hurn 2010). We note that Eq.…”
Section: Introductionsupporting
confidence: 75%
“…2 for the two example clusters. Andreon (2015) showed that results do not change when using another number of iterations because convergence is achieved earlier, whereas in Sect. 4 we show that the starting position does not matter when using duplicate clusters (objects with center offsets larger than 3 arcmin in different cluster catalogs, and therefore listed twice in our initial list of clusters to be analyzed).…”
Section: Cluster Sample and Derivation Of Cluster Richness And Massmentioning
confidence: 96%
“…The large variety is indirectly confirmed by Andreon & Moretti (2011), who observed a 0.5 dex scatter at a given richness, which is known to be a low scatter proxy of mass (e.g., Andreon & Hurn 2010;Andreon 2015). That sample, however, lacks direct measurements of mass.…”
Section: X-ray Luminosity Vs Massesmentioning
confidence: 79%
“…Observations also indicate that caustic masses cannot be much noisier than their quoted error (i.e., cannot have have understimated errors) because they correlate with almost no scatter with richness (Andreon 2015), which in turns correlates with almost no scatter with weak-lensing mass (Andreon & Congdon 2014). This latter correlation adopts fixed-aperture masses and, therefore, the source of the tight relation cannot be an effect introduced using mass-related apertures such as r 200 .…”
Section: Is Variety Due To Wrong Cluster Masses?mentioning
confidence: 96%
“…membership_paper_AA_corrected_for_editing_after_proofs (2015); Saro et al (2015); Bocquet et al (2016). The cluster richness is also used as independent cluster mass proxy (e.g., Andreon 2015). Robust membership assignments can be exploited to estimate the richness ; however, the correct identification of both field sources and cluster members is needed.…”
Section: Introductionmentioning
confidence: 99%